Погребения детей в могильнике Нейзац - Храпунов, И.Н. (Материалы по археологии, истории и этнографии Таврии, 2006)
В данной статье публикуются результаты раскопок погребальных сооружений, предназначенных специально для погребения детей. Они дают возможность охарактеризовать «детскую субкультуру» населения крымских предгорий позднеримского времени. The cemetery of Neizatz is situated in the centre of the Crimean foothills at the distance of about 25 kms to the south-east from Simferopol, 1-1,5 kms to the southeast from the village of Balanovo, Belogorsk district of the Autonomous Republic of Crimea. It occupies the lower part of the slope of Tashlu-Bair Mountain which bounds the valley of Zuja river in the east. Systematic excavations of the monument have been carried out since 1996. 299 burial constructions were excavated, among them vaults, shaft-and-chamber and underground graves. The results of the excavations of some burial constructions have already been published; however, there are no children’s burials among them. Meanwhile, children had been buried in all types of burial constructions during the whole period of using the cemetery. Children’s burials were revealed in separate graves as well, and together with adults. The results of excavations of burial constructions specially designed for burying children are published in this article. They enable us to characterize “children’s subculture’ of the population of the Crimean foothills dating to Late Roman period.